2017
DOI: 10.1002/jcla.22189
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelets volume and neutrophil to lymphocyte ratio as predictors of stroke

Abstract: Background Mean platelets volume (MPV) is a marker, which indicates platelet function, and is a potential link between inflammation and thrombosis. Previous studies have found a relation between high MPV levels and high risk of stroke. Another factor that has been associated with the risk of stroke is neutrophil to lymphocyte ratio (NLR). Several studies have reported an association between increased NLR and increased risk of cerebrovascular disease. It was found that NLR levels have a relation to the prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Seventeen results of the 27 studies revealed that patients with stroke had higher MPV than controls [10,12,25,27,28,34,35,39,41-43, [46][47][48]50]. Ten studies found no difference in MPV between patients and controls [14,15,28,29,35,36,38,45,49], and two studies demonstrated a higher MPV in the control group (Table I, Supplementary Table VI) [13,40]. The mean MPV for all publications was 9.8 fL (95% CI 9.4-10.1) for patients and 9.2 fL (95% CI, 8.8-9.6) for controls.…”
Section: Mpvmentioning
confidence: 99%
“…Seventeen results of the 27 studies revealed that patients with stroke had higher MPV than controls [10,12,25,27,28,34,35,39,41-43, [46][47][48]50]. Ten studies found no difference in MPV between patients and controls [14,15,28,29,35,36,38,45,49], and two studies demonstrated a higher MPV in the control group (Table I, Supplementary Table VI) [13,40]. The mean MPV for all publications was 9.8 fL (95% CI 9.4-10.1) for patients and 9.2 fL (95% CI, 8.8-9.6) for controls.…”
Section: Mpvmentioning
confidence: 99%
“…These different markers give information about platelet sizes and platelet functions . During activation, the platelet size tends to increase, and the platelets become hemostatically more active than small platelets . MPV, usually used to measure the platelet size, is an important biomarker of platelet activation and function .…”
Section: Introductionmentioning
confidence: 99%
“…The reason why we had different results may be related to the fact that we included cases with a specific disease. In one study, Farah and Samra [36] compared NLR and MPV values between cases diagnosed with ischemic stroke and 30 healthy volunteers, and they found higher NLR values in cases with ischemic stroke compared to healthy volunteers, whereas they did not find difference in MPV values. Farah and Samra [36] proposed that NLR was a good predictor for stroke and prognosis of stroke, while MPV was not [36].…”
Section: Discussionmentioning
confidence: 42%